Influence of natural organic additives on the resistance to salt crystallization in traditional lime mortars with different arid. Case analysis: La Blanca archaeological site, Petén, Guatemala - Lorenzo Mora, Francisca (2019)
La Blanca is a Terminal Classic period Mayan settlement, located in the Petén jungle of Guatemala. In the imposing rooms that form the Acropolis, there were found much of the stucco which formed the inner lining, even with traces of colour. Since these rooms were excavated, the stuccos have been affected by the water that rises by capillarity and the salts crystallization, both on the surface and in the stone support, which has caused serious pathologies such as laminations and material disintegration. For this reason, laboratory studies are being carried out with different lime mortars that can be used in the restoration with full guarantee. In this paper, the comparative results of stability against salts crystallization cycles on two kind of traditional lime mortars are presented, and the influence that organic additives have on the improvement of resistance is evaluated.